Permintaan Daun Pisang pada Produsen Nasi Jinggo di Kota Denpasar - GUNAWAN, DEFRY SANJAYA; WIDYANTARA, I WAYAN; BUDIASA, I WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
The Demand for Banana Leaves by the Jinggo Rice Producers in Denpasar City This study aims to determine the number of banana leaves demand by the jinggo rice producers in a period of one week, the factors that affect the demand of banana leaves, and to investigate the substitute of banana leaves used by sellers as a jinggo rice wrapper. The research location was in Denpasar City determined by purposive sampling. The population in this research was all of the jinggo rice sellers in Denpasar City. The sampling technique used snowball sampling method. This research used tabulation to find out the demand of banana leaves discussed descriptively and qualitatively and by using regression equation which is transformed to analyze the influencing factors. The results of this study indicate that the total number of banana leaves demand by 40 respondents of jinggo rice sellers in Denpasar, within one week is equal to 7,822 folds or as many as 23,466 banana leaf bark. Factors affecting the demand of banana leaves from the jinggo rice sellers in Denpasar City were the price of banana leaves and the amount of production, and there is no substitute for banana leaves used by the 40 jinggo rice sellers in Denpasar City.